Exposed [compact disc, unabridged] - Scottoline, Lisa (Scottoline, Lisa. Rosato & DiNunzio novel., 2017)
Deciding to represent opposing sides in a wrongful termination lawsuit, DiNunzio and Rosato face conflict of interest complications that force their friends and colleagues to take sides.